SPIRITUALITY AND SOCIAL STRESS: AN ANTHROPOLOGICAL STUDY OF RELIGIOUS BELIEFS AND SPIRITUAL PRACTICES IN PAKISTAN - Majid Hussain Alias Ghalib Hussain; Hifza Nisar; Dr. Atifa Nasir (International Journal of Contemporary Issues in Social Sciences, 2024)
Social stress is part of the life of every individual. This qualitative study analyses the interrelationship between spirituality and social stress. The study finds that the respondents had strong religious beliefs on spirituality to overcome social stress. The respondents performed various spiritual practices to deal with different forms of social stress. This study was conducted in Rawalpindi and Islamabad and through convent and purposive sampling techniques two hospitals and three shrines were selected for this study. A sample of 46 respondents was selected to conduct in-depth interviews. An unstructured interview guide was developed to collect narratives about the respondents’ social sufferings, spiritual beliefs, and spiritual practices. The respondent’s information was crosschecked and verified through participant observations in the hospital settings and selected shrines. Field data reveals that spirituality was a common practice for the protection of the evil eye, to reduce the pain of patients in hospitals, to wish for easy death for terminal-stage patients, and to overcome unforeseen fear. The study reported internal peace and calmness among the respondents. This research answers the research question that spirituality reduces social stress and the respondents had a strong belief in spiritual practices.